Comparison between the estimated and actual productivity for the fabrication of a steel framework / Mohd Zukarnan Mat Deraseh - Mat Deraseh, Mohd Zukarnan (2010)
A manufacturing company has the need to improve productivity in fabrication. The improvement in production technology will not effectively increase productivity unless the efficiency in material handling, preparation, assembly, application of tooling and welding deposition is optimized. To improving the productivity, Work Study analysis was applied, incorporating Method Study and Work Measurement to determine the critical path, to optimize the assembly line and to eliminate activities that reduce the productivity. The study began by selection one of the process line (fabrication of structure frame), video of the entire process or activities such as design of the structure frame with Catia software(structure details, gusset details, welding details, bolting details)welding training, structure members(search material, handling material, measurement of material preparation of cutting process, replace material, drilling), gusset plate(search, handling, cutting, replace, drilling material), assembly(assembly the fixture, assembly the structure members, assembly the gusset plate, tack welding/bolting) and welding(preparation of welding machine, preparation of frame before welding, NDT testing, inspecting of welding) was recorded and data were analyzed in Microsoft project software. Through replay of the video, the duration of every operation step in every work station can be measured. Based on the production flow, a new flow chart was developed in Microsoft Project software, a planned project schedule or new flow chart will then be compared to actual fabrication performance.